The impact of physical exercise on convergent and divergent thinking - Colzato, Lorenza S.; Szapora Ozturk, Ayca; Pannekoek, Justine N.; Hommel, Bernhard (Frontiers in Human Neuroscience, 2013)
Anecdotal literature suggests that creative people sometimes use bodily movement to help overcome mental blocks and lack of inspiration. Several studies have shown that physical exercise may sometimes enhance creative thinking, but the evidence is still inconclusive. In this study we investigated whether creativity in convergent- and divergent-thinking tasks is affected by acute moderate and intense physical exercise in athletes (n = 48) and non-athletes (n = 48). Exercise interfered with divergent thinking in both groups. The impact on convergent thinking, the task that presumably required more cognitive control, depended on the training level: while in non-athletes performance was significantly impaired by exercise, athletes showed a benefit that approached significance. The findings suggest that acute exercise may affect both, divergent and convergent thinking. In particular, it seems to affect control-hungry tasks through exercise-induced “ego-depletion,” which however is less pronounced in individuals with higher levels of physical fitness, presumably because of the automatization of movement control, fitness-related neuroenergetic benefits, or both.